Abutting left atrial appendage and left superior pulmonary vein predicts recurrence of atrial fibrillation after point-by-point pulmonary vein isolation. (24th May 2021) - Szegedi, N; Simon, J; Szilveszter, B; Sallo, Z; Herczeg, S; Nagy, VK; Szeplaki, G; Tahin, T; Merkely, B; Geller, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Catheter ablation is the cornerstone for rhythm control in patients with drug-refractory atrial fibrillation (AF). Baseline predictors of AF recurrence after catheter ablation are well established, such as female gender and left atrial enlargement. The role of the spatial relationship between the left superior pulmonary vein (LSPV) and left atrial appendage (LAA) is unknown. Purpose: We sought to evaluate whether juxtaposed LSPV and LAA plays a role in AF recurrence after catheter ablation for paroxysmal AF. Methods: Consecutive patients, who underwent point-by-point radiofrequency catheter ablation for paroxysmal AF at our hospital between January of 2014 and December of 2017, were enrolled in the study. All patients underwent pre-procedural cardiac CT-angiography (CTA) for the assessment of left atrial (LA) and pulmonary vein (PV) anatomy. Abutting LAA-LSPV was defined as cases when LSPV touched the posterior aspect of LAA (distance less than 2 mm). Results: We included 428 patients (60.7 ± 10.8 years, 35.5% female). AF recurrence rate was 33.4% with a median recurrence-free time of 21.2 (IQR = 8.8-43.0) months. In the univariate analysis, female sex (HR = 1.45; 95%CI = 1.04-2.01; p = 0.028), LA volume (HR = 1.01; 95%CI = 1.00-1.01; p = 0.042), and cases when LSPV touched the posterior wall of LAA (HR = 1.53; 95%CI = 1.09-2.14; p = 0.013) were associated with AF recurrence. In the multivariate analysis, female sex (adjusted HR = 1.55; 95%CI = 1.06-2.28; p = 0.024), LA volume (adjusted HR = 1.01; 95%CI = 1.00-1.02; p = 0.028), and abutting LAA-LSPV (adjusted HR = 1.60; 95%CI = 1.13-2.50; p = 0.008) remained significant predictors of AF recurrence. Conclusion: Female gender, higher LA volume, and abutting LSPV and LAA predispose patients to have a higher chance for arrhythmia recurrence after catheter ablation for paroxysmal AF.